From Honfleur to Cape Verde. A new look at Georges Bissipat, “the Greek’s”, 1483 voyage - (:unkn) unknown (My University, 2018)
Comparing Thomas Basin and Eustache Delafosse’s accounts, Charles de la Roncière considered that Georges Bissipat was seeking to bring back turtles to cure Louis XI who thought he was suffering from leprosy. This very expensive expedition that sailed from Honfleur must, however, take into account the European diplomatic context in which João II sought to bar all other European nations from trade with Africa. The 1483 French expedition illustrates the French king’s determination to defy exclusive Portuguese claims.
Keywords: African Research